2012
DOI: 10.1016/j.pedneo.2011.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Herlyn-Werner-Wunderlich Syndrome Consisting of Uterine Didelphys, Obstructed Hemivagina and Ipsilateral Renal Agenesis in a Newborn

Abstract: Herlyn-Werner-Wunderlich (HWW) syndrome is a rare variant of Müllerian duct anomalies consisting of uterine didelphys, obstructed hemivagina, and ipsilateral renal agenesis. Patients with HWW syndrome are usually asymptomatic until menarche, when they present with acute lower abdominal pain. Here we report a case of a female newborn with right renal agenesis diagnosed during the pregnancy. The patient presented with a protruding mass over the vaginal introitus that was associated with an obstructed hemivagina … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
52
0
15

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 10 publications
1
52
0
15
Order By: Relevance
“…Se produce alrededor de la novena semana de gestación, por un fallo en la fusión de los conductos de Müller verticales y laterales. Su etiología es desconocida y se caracteriza por la tríada de útero didelfo, hemivagina obstruida y agenesia renal unilateral 3 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Se produce alrededor de la novena semana de gestación, por un fallo en la fusión de los conductos de Müller verticales y laterales. Su etiología es desconocida y se caracteriza por la tríada de útero didelfo, hemivagina obstruida y agenesia renal unilateral 3 .…”
Section: Discussionunclassified
“…Aunque la utilidad de esta técnica para el tratamiento quirúrgico no está clara, sí puede ayudar al drenaje del hematocolpos y/o al tratamiento de las complicaciones ya descritas 3,5 .…”
Section: Discussionunclassified
“…Most patients present with non-specific postpubertal symptoms, generally from 2 to 12 months after menarche [19]. In a study including 70 patients with HWWS, Tong et al [1] reported a mean age at onset of symptoms of 17 years, ranging from 10 to 44.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…So, the prepubertal diagnosis of the HWWS generally implies a high index of suspicion, which may come from prenatal or neonatal renal US. If renal agenesis is found in prenatal or neonatal US, particular attention should be provided to the external genitalia and, even in the absence of a pelvic or vulvar mass, the risk of further genital anomaly should be highlighted [19].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Fizik muayenede sağ tarafta daha sık olmak üzere tek taraflı pelvik kitle saptanır. 8 Ancak bizim olgumuz, sol obstrükte hemivajen ve sol hematokolposa bağlı pelvik kitle ile prezente olmuştur. Piyohematokolpos, piyosalpenks, piyoperitonit gibi enfektif süreçler, retrograd menstrüasyona sekonder endometriyoz ve pelvik adezyonlar karşılaşılabilecek komplikasyonlar arasındadır.…”
unclassified